A CTAB-mediated antisolvent vapor route to shale-like Cs4PbBr6 microplates showing an eminent photoluminescence. Issue 17 (9th March 2020) - Wei, Yunwei; Zheng, Wei; Shahid, Malik Zeeshan; Jiang, Zhixiang; Li, Yuehua; Duan, Zhongyao; Liu, Guangning; Hu, Xun; Li, Cuncheng
Abstract : Highly luminescent shale-like Cs4 PbBr6 microplates with hundreds of microns in lateral dimension and formed by thin nanosheets with orientational stacking. Abstract : Compared with nanoscale quantum dots (QDs), the large-sized perovskite crystals not only possess better stability but also are convenient for application exploration. Herein, we develop a facile and efficient antisolvent vapor-assisted recrystallization approach for the synthesis of large-sized Cs4 PbBr6 perovskite crystal microplates. In this method, for the first time, the shale-like Cs4 PbBr6 microplates with lateral dimensions of hundreds of microns are fabricated by employing cetyltriethylammnonium bromide (CTAB) as a morphology-directing agent. FESEM, TEM, and AFM characterizations indicate that the as-obtained shale-like Cs4 PbBr6 microplates are actually formed by 6–8 nm thick Cs4 PbBr6 nanosheets with orientational stacking. Importantly, such highly crystalline Cs4 PbBr6 microplates with shale-like morphology exhibit a narrow and intense green PL emission with a 59% PL quantum yield. Moreover, the planar structure of shale-like Cs4 PbBr6 microplates makes it easy to form a preferred orientation on a substrate, which endow them with promising potential in optoelectronic devices such as lighting and displays.